Coronary Heart Disease and Fish Oil - Spivack, MD, Talya (The Medicine Forum, 2011)
Introduction The benefits of fish consumption on cardiovascular disease has been suggested since the early 1980s in studies that demonstrated Greenland Eskimo’s low rates of death from coronary heart disease.1 This was followed by another observational study that demonstrated the same findings in Japan.2 The proposed linkage between these two groups of people is their propensity to consume fish. Since then many studies have examined the relationship between fish consumption and coronary heartdisease (CHD) mortality rates. Current thinking suggests that the primary benefit of consuming fish is secondary to the omega-3 fatty acids found in fish oil.